Using Tax Incentives to Compete for Foreign Investment : Are They Worth the Costs? - Wells, Louis T., Jr. (Washington, DC: World Bank and the International Finance Corporation, 2013)
The book contains complementary essays on the use of tax incentives, to attract foreign direct investment (FDI). The first essay presents results of the authors' original research, and explores FDI, and issues of tax incentives, in the context of Indonesia. Their results mostly support the arguments made against incentives, particularly they find little evidence that when Indonesia eliminated tax incentives, there was any decline in the rate of FDI into the country. Similarly, the second essay surveys the research of others on the same topic, and pertaining to the same issues discussed in the first essay. They show that results of other researchers, are generally consistent with the findings of the research in Indonesia, notably that tax incentives, neither affect significantly the amount of direct investment that takes place, nor usually determine the location to which investment is drawn. Nevertheless, recent evidence has shown that when factors such as political, and economic stability, infrastructure, and transport costs are more, or less equal between potential locations, taxes may exert a significant impact. This is evidenced by the growing tax competition in regional groupings (i.e., the European Union) or, at the sub-regional level within one country (i.e., the United States). Both essays provide a basis for much more sophisticated analysis by policymakers than previously, and, both are important because they question governments' institutional arrangements that create agency problems with respect to tax incentive policies.